Difference between revisions of "Floyd's cycle-finding algorithm"

From HaskellWiki
Jump to: navigation, search
(Simplify pattern-matching equations.)
(elements must be unique, e.g. findCycle $ cycle [0,1,0])
Line 15: Line 15:
 
</haskell>
 
</haskell>
   
This function is essentially the inverse of <hask>cycle</hask>. I.e. if <hask>xs</hask> and <hask>ys</hask> don't have a common suffix and both are finite, we have that
+
This function is essentially the inverse of <hask>cycle</hask>. I.e. if <hask>xs</hask> and <hask>ys</hask> don't have a common suffix, their elements are unique and both are finite, we have that
 
<haskell>
 
<haskell>
 
findCycle (xs ++ cycle ys) == (xs,ys)
 
findCycle (xs ++ cycle ys) == (xs,ys)

Revision as of 16:38, 17 October 2011

This is a Haskell impelementation of Floyd's cycle-finding algorithm for finding cycles in lists.

findCycle :: Eq a => [a] -> ([a],[a])
findCycle xxs = fCycle xxs xxs
  where fCycle (x:xs) (_:y:ys)
         | x == y              = fStart xxs xs
         | otherwise           = fCycle xs ys
        fCycle _      _        = (xxs,[]) -- not cyclic
        fStart (x:xs) (y:ys)
         | x == y              = ([], x:fLength x xs)
         | otherwise           = let (as,bs) = fStart xs ys in (x:as,bs)
        fLength x (y:ys)
         | x == y              = []
         | otherwise           = y:fLength x ys

This function is essentially the inverse of cycle. I.e. if xs and ys don't have a common suffix, their elements are unique and both are finite, we have that

findCycle (xs ++ cycle ys) == (xs,ys)